2016
DOI: 10.1128/jvi.03242-15
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-33a-5p Modulates Japanese Encephalitis Virus Replication by Targeting Eukaryotic Translation Elongation Factor 1A1

Abstract: Japanese encephalitis virus (JEV) is a typical mosquito-borne flavivirus responsible for acute encephalitis and meningitis in humans. However, the molecular mechanism for JEV pathogenesis is still unclear. MicroRNAs (miRNAs) are small noncoding RNAs that act as gene regulators. They are directly or indirectly involved in many cellular functions owing to their ability to target mRNAs for degradation or translational repression. However, how cellular miRNAs are regulated and their functions during JEV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 50 publications
0
45
0
1
Order By: Relevance
“…Moreover, the viral replicase complex is important in virus replication, and eukaryotic translation elongation factor 1A1 (EEF1A1) can stabilize the components of the viral replicase complex. The downregulation of host miR-33a-5p during Japanese encephalitis virus infection enhances virus replication resulting from the upregulation of the EEF1A1 gene, the target gene of miR-33a-5p (14). Furthermore, during virus infection, apoptosis of host cells can be triggered to inhibit virus invasion.…”
mentioning
confidence: 99%
“…Moreover, the viral replicase complex is important in virus replication, and eukaryotic translation elongation factor 1A1 (EEF1A1) can stabilize the components of the viral replicase complex. The downregulation of host miR-33a-5p during Japanese encephalitis virus infection enhances virus replication resulting from the upregulation of the EEF1A1 gene, the target gene of miR-33a-5p (14). Furthermore, during virus infection, apoptosis of host cells can be triggered to inhibit virus invasion.…”
mentioning
confidence: 99%
“…Specifically,

hsa-miR-892b is member of miR-888 gene family that has restricted expression in adult testicular germ cells. They are known as Cancer-testis (CT) antigens which are clustered near the end of the long arm of the X chromosome (Xq27-Xq28) and contain several reported miRNAs like hsa-miR-888, hsa-miR-890, hsa-miR-891a, hsa-miR-891b, hsa-miR-892a, and hsa-miR-892b [6870];

hsa-miR23a and hsa-miR-23b are involved in epididymal maturation of sperm and express in epididymides [71]; hsa-miR-33 *—including both hsa-miR-33a and hsa-miR-33b —has been shown to be differentially expressed in testes [72]; moreover, according to [73] hsa-miR-33a-5p directly targets EEF1A1; hsa-miR-148a and hsa-miR-148b have been found to affect the modification of susceptibility to oligozoospermia [74];by comparing fertile and infertile populations of men hsa-miR-152-3p has been found to be correlated with sperm concentration [75]; miR-181b and miR-181c were found up-regulated in adult in mouse testis tissue [76], and are involved in transcriptional regulation in haploid germ cells by targeting rsbn1, a gene postulated to be involved in transcriptional regulation in haploid germ cells; miR-155 and miR-146a have been found to be present in male serum [77] and to be correlated with each other; however, while miR-155 is associated with male sub-fertility independent of Low-Grade Systemic Inflammation (LGSI) or androgens, miR-146a is only weakly associated with sub-fertility and LGSI;by comparing miRNA expression patterns for abnormal semen from infertile males and normal semen from healthy males, hsa-miR-130a has been found to be significantly under-expressed in the abnormal semen compared with the normal semen [78].
…”
Section: Resultsmentioning
confidence: 99%
“…hsa-miR-33 *—including both hsa-miR-33a and hsa-miR-33b —has been shown to be differentially expressed in testes [72]; moreover, according to [73] hsa-miR-33a-5p directly targets EEF1A1;…”
Section: Resultsmentioning
confidence: 99%
“…However, the defense function of host miRNAs can be counteracted by viral suppressors of RNA silencing (VSRs) that inhibit host antiviral responses by interacting with the critical components of cellular RNA silencing machinery or direct participate the host RNA degradation (6, 26). Recently, an increasing number of studies have found that JEV infection were capable of regulating functional miRNAs (3, 14, 53, 60, 61, 73). Although plenty of works were examined the host biogenesis regulating by miRNA during the viral infection process, relatively little was known about regulation of miRNA by JEV.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-155, miR-15b miR-19b and miR-29b are induced and activated innated immune response after JEV infection, respectively (3, 60, 61, 73). Beside JEV infection reduces the expression of miR-33a and miR-432 to facilitate virus replication (14, 53). Therefore, the regulation of miRNA is important for cell biological process and mRNA homeostasis during the JEV infection.…”
Section: Introductionmentioning
confidence: 99%